Identification of a novel steroid inducible gene associated with the ?hsd locus of Comamonas testosteroni (2004)
Comamonas testosteroni is a soil bacterium, which can use a variety of steroids as carbon and energy source. Even if it can be estimated that the complete degradation of the steroid nucleus requires more than 20 enzymatic reactions, the complete molecular characterization of the genes encoding these steroid degradative enzymes as well as the genetic organization of them remain to be elucidated. We have previously reported the cloning and nucleotide sequence of two steroid-inducible genes, ?hsd and stdC encoding 3?-17?-hydroxysteroid dehydrogenase and a hypothetical protein respectively, located in both ends of a 3.2 kb HindIII fragment. Herein, we report the cloning and characterization of another steroid-inducible gene, called sip48 (steroid inducible protein), located between these two genes. The analysis of Sip48 amino acid sequence predicts a protein of 438 amino acids with a molecular mass of 48.5 kDa. This protein bears high homology with conserved hypothetical proteins of unknown function described in Pseudomonas aeruginosa, Pseudomonas syringae, Pseudomonas putida, Burkholderia fungorum, Shewanella oneidensis, Pseudomonas fluorescens and Thauera aromatica. The predicted protein shows a typical structure of a leader peptide at its N-terminus. A 48.5 kDa protein encoded by the recombinant plasmid was detected by SDS–PAGE analysis of in vitro []-methionine labeled polypeptides. Analysis of gene expression indicates that Sip48 is tightly controlled at the transcriptional level by several steroid compounds. In addition, transcriptional analysis of sip48 and ?hsd in a sip48 mutant strain, indicates that both genes are transcribed as a polycistronic mRNA. lacZ transcriptional fusions integrated into the chromosome of C. testosteroni demonstrate that a steroid-inducible promoter located upstream of sip48 regulates the expression of both genes.